2021
DOI: 10.5194/esurf-9-673-2021
|View full text |Cite
|
Sign up to set email alerts
|

Precise water level measurements using low-cost GNSS antenna arrays

Abstract: Abstract. We have developed a ground-based Global Navigation Satellite System Reflectometry (GNSS-R) technique for monitoring water levels with a comparable precision to standard tide gauges (e.g. pressure transducers) but at a fraction of the cost and using commercial products that are straightforward to assemble. As opposed to using geodetic-standard antennas that have been used in previous GNSS-R literature, we use multiple co-located low-cost antennas to retrieve water levels via inverse modelling of signa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Their unit total cost, including solar power, was ∼ $200 U.S. dollars. Purnell et al (2021) employed a stack of side-facing low-cost antenna and receivers (total cost ∼ $200-300 U.S. dollars including solar panel and battery) to track the L1 frequency of multiple GNSS constellations. The water surface reflections extended more than 140° in azimuth and over a range of elevation angles up to 50°.…”
Section: Low-cost Gnss-ir Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…Their unit total cost, including solar power, was ∼ $200 U.S. dollars. Purnell et al (2021) employed a stack of side-facing low-cost antenna and receivers (total cost ∼ $200-300 U.S. dollars including solar panel and battery) to track the L1 frequency of multiple GNSS constellations. The water surface reflections extended more than 140° in azimuth and over a range of elevation angles up to 50°.…”
Section: Low-cost Gnss-ir Unitmentioning
confidence: 99%
“…Such installations have far superior reflection characteristics at the cost of poor positioning capabilities. GNSS‐IR also benefits from using an inexpensive GNSS antenna which does not mitigate reflections to the same extent as larger geodetic antenna (Fagundes et al., 2021; Purnell et al., 2021; Williams et al., 2020).…”
Section: Gnss Interferometric Reflectometry For Water Level Measurementsmentioning
confidence: 99%
“…Recently it has become clear that compact, low‐cost (or mass‐market) GNSS antennas and receivers, such as those that are embedded in mobile devices, may be better suited for GNSS‐IR water level monitoring than geodetic‐standard antennas (Fagundes et al., 2021; Karegar et al., 2022; D. J. Purnell et al., 2021; Williams et al., 2020). Geodetic‐standard antennas are designed to reduce the interference from reflected GNSS signals, while the low‐cost antennas are not (it should be noted that the low‐cost antennas do not perform as well as geodetic‐standard antennas for positioning applications).…”
Section: Introductionmentioning
confidence: 99%
“…In D. J. Purnell et al. (2021) (henceforth DP21), the authors found that using multiple co‐located low‐cost antennas was an effective way to reduce the effect of random noise—a key source of uncertainty in GNSS‐IR water levels (D. Purnell et al., 2020)—and hence improve the precision of water levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation